2002
DOI: 10.1051/0004-6361:20020672
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the photometric and dynamical behavior of Super-Schmidt meteors in the Earth's atmosphere

Abstract: Abstract. Faint meteors observed with Super-Schmidt cameras are re-examined in order to assess whether their dynamical and photometric behavior can be described by means of the single body theory. Velocities, decelerations and magnitudes are fitted simultaneously to synthetic curves resulting from integration of the appropriate set of differential equations. The parameters determined by this procedure are the ablation coefficient, the shape-density coefficient and the preatmospheric mass of each individual met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 21 publications
4
38
0
Order By: Relevance
“…Such task is very difficult and the results are model dependent. There is, nevertheless, an agreement that Geminids contain the meteoroids with highest density of all showers (Babadzhanov 2002;Bellot Rubio et al 2002). Other meteoroids with relatively high density are δ-Aquariids and Quadrantids (Babadzhanov 2002).…”
Section: Meteor Datamentioning
confidence: 95%
“…Such task is very difficult and the results are model dependent. There is, nevertheless, an agreement that Geminids contain the meteoroids with highest density of all showers (Babadzhanov 2002;Bellot Rubio et al 2002). Other meteoroids with relatively high density are δ-Aquariids and Quadrantids (Babadzhanov 2002).…”
Section: Meteor Datamentioning
confidence: 95%
“…He also divided group C into three subgroups based on orbital elements, but due to our small number statistics, we treat these as one. Equation (5) was developed and first applied to meteors photographed by Super-Schmidt cameras (see Ceplecha 1967Ceplecha , 1988Bellot Rubio et al 2002). For the fainter meteors observed by intensified video systems, the parameter K B is calculated in the same way, but an offset of 0.15 is added (see Ceplecha 1988) because the K B criterion is based on meteor beginning heights, which depend on the sensitivity of the camera.…”
Section: Comparison Using the K B Parametermentioning
confidence: 99%
“…To account for this, he introduced the concept of progressive fragmentation (meteoroids fragment progressively into smaller pieces during atmospheric flight). Bellot Rubio et al (2002) found that visible forms of fragmentation (wake and terminal blending) can be present in the lightcurves of some faint meteors showing deceleration anomalies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations